Freestyle - Galligan, Gale, ....-; CZap, K., ....- (New York : Graphix - Schoolastic, 2022)
From New York Times bestselling author Gale Galligan, a fun, high-energy graphic novel about friendship, family, and the last hurrahs of middle school. Cory's dance crew is getting ready for a major competition. It's the last one before they graduate eighth grade and go their separate ways to high schools all over New York City, so they have to make it count! The group starts to have problems as their crew captain gets increasingly intense about nailing the routine, and things go from bad to worse when Cory's parents ground him for not taking his grades seriously. He gets stuck with a new tutor, Sunna, who he dismisses as a boring nerd... until he catches her secretly practicing cool yo-yo tricks. Cory wants to learn the art of yo-yo, and as his friendship with Sunna grows, he ends up missing practice and bailing on his crew -- and they are not happy about it. With mounting pressure coming from all sides, how is Cory supposed to balance the expectations of his parents, school, dance, and his new friend?
Keywords: Breakdance; Engels; Graphic novels; Secundair onderwijs; Stripverhaal